PENGARUH PENATAUSAHAAN DAN PENERTIBAN BARANG MILIK DAERAH TERHADAP PENGAMANAN BARANG MILIK DAERAH DIMODERASI SPIP PADA PEMERINTAH KABUPATEN MANDAILING NATAL - Lubis, Tolha Aminah; Sari, Eka Nurmala; Hariani, Prawidya (Worksheet : Jurnal Akuntansi, 2025)
The purpose of this research is to investigate and evaluate how the administration and regulation of regional assets affect asset security, with the Government Internal Control System (SPIP) serving as a moderating factor within the Mandailing Natal Regency Government. This study applies a quantitative associative approach through the distribution of questionnaires, using a saturated sampling method and path analysis facilitated by SEM PLS software version 4. A total of 62 respondents participated in this study. The findings reveal that proper administration of regional assets significantly enhances asset security, meaning that better administrative practices contribute to stronger safeguarding of assets. Likewise, the regulation and enforcement of asset management positively influence the protection of regional assets. Furthermore, the results show that SPIP moderates both the relationship between asset administration and asset security, as well as the relationship between asset regulation and asset security.